Enrichment of rare CFTR variants in Finnish patients with congenital chloride diarrhea - Satu Wedenoja; Jarmo Ritari; Jukka Partanen; Juha Kere; Kaija-Leena Kolho (PLoS ONE, 2025)
Objective The autosomal recessive disease congenital chloride diarrhea (CLD), caused by loss-of-function mutations in the solute carrier family 26 member 3 (SLC26A3) gene, shows association with inflammatory bowel disease (IBD). However, it is unclear whether IBD risk is associated with genetic or immune signatures. SLC26A3 interacts with several ion transporters linked to intestinal inflammation, such as cystic fibrosis transmembrane conductance regulator (CFTR) and solute carrier family 9 member 3 (SLC9A3) causing congenital sodium diarrhea. We hypothesized that other epithelial channels affecting intestinal salt balance might modulate CLD phenotype or IBD risk. Materials and methods We analyzed 495 gene variants within 33 ion transporters among 28 patients with CLD and 44,443 population controls. Results We found three intronic variants at or near the CFTR locus (rs17132543, rs2283054 and rs76622533) showing statistically significant (P < 1.42x10-5) associations with CLD. Conclusions These data demonstrate enrichment of rare variants at the CFTR locus in chromosomes harboring the Finnish founder mutation for CLD.